2008
DOI: 10.1111/j.1365-2486.2008.01607.x
|View full text |Cite
|
Sign up to set email alerts
|

Missing methane emissions from leaves of terrestrial plants

Abstract: The controversial claim that attached leaves of terrestrial plants emit CH 4 aerobically remains to be corroborated. Here, we report CH 4 fluxes and CO 2 exchange rates for leaves of the C 4 species Zea mays using a high-accuracy traceable online analytical system. In contrast to earlier results for Z. mays, our measurements provide no evidence for substantial aerobic CH 4 emissions from photosynthesizing leaves illuminated with photosynthetically active radiation (k 5 400-700 nm), or from dark-respiring leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 24 publications
3
39
1
Order By: Relevance
“…Several studies have reported opposite results that no measurable CH 4 release from plants was detected (Beerling et al, 2008;Bowling et al, 2009;Dueck et al, 2007;Kirschbaum and Walcroft, 2008;Nisbet et al, 2009;Smeets et al, 2009;Takahashi et al, 2012). One potential explanation for the absence of CH 4 emissions is that the CH 4 produced was consumed by endophytic methanotrophs.…”
Section: Uncertainties and Limitationsmentioning
confidence: 85%
“…Several studies have reported opposite results that no measurable CH 4 release from plants was detected (Beerling et al, 2008;Bowling et al, 2009;Dueck et al, 2007;Kirschbaum and Walcroft, 2008;Nisbet et al, 2009;Smeets et al, 2009;Takahashi et al, 2012). One potential explanation for the absence of CH 4 emissions is that the CH 4 produced was consumed by endophytic methanotrophs.…”
Section: Uncertainties and Limitationsmentioning
confidence: 85%
“…The first follow-up study (Dueck et al, 2007) did not confirm the findings: No 13 CH 4 emissions were found from plants, which were grown in a 13 CO 2 atmosphere and should thus have produced 13 CH 4 only. Beerling et al (2008) similarly reported no CH 4 emissions from a C3 and a C4 species but suggested a possible role of nonenzymatic processes with an action spectrum outside the photosynthetically-active range. Nevertheless, to the best of our knowledge there is no scenario other than direct emissions from the plant matter that can explain the (natural abundance) isotope signatures observed in the earlier experiments by Keppler et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies (Dueck et al, 2007;Beerling et al, 2008;Kirschbaum and Walcroff, 2008;Nisbet et al, 2009) observed no substantial aerobic CH 4 emission from plants. However, six independent studies McLeod et al, 2008;Vigano et al, 2008;Wang et al, 2008;Brüggemann et al, 2009;Messenger et al, 2009) did detect CH 4 emission from plant tissues/compounds under aerobic conditions in the laboratory.…”
Section: Introductionmentioning
confidence: 99%